Regional planning in Libya: Regional planning in Libya (jornal of the libyan geographical society, 2016)
Planning focuses on organizing and regulating individual and collective activities to minimize potential negative impacts, as well as achieving a better natural environment within the framework of implementing the objectives of the approved plan. Given the crucial relationship between planning and the human being (the planner), their participation in the planning process is essential.This is of paramount importance because of the positive outcomes this participation brings to planning programs that integrate the aspirations of the people with the economic and natural resources of each country.The need for regional planning arose from the disparities between different regions and areas within a single country, resulting from unbalanced development. This is due to...The uneven distribution of development projects, with industrial and service projects concentrated in major cities, has exacerbated the disparity in income and living standards between urban and rural populations. These differences have led to various problems.The high population density in cities leads to increased demand for services such as housing, transportation, utilities, and other amenities. Conversely, the lack of services and the resulting low population density in rural areas contribute to decreased agricultural production.
Keywords: Planning; Individual activities; Approved plans; Planning and people; Unbalanced distribution; Industrial projects; Service projects